Luta por moradia em Erechim / RS: a ação do movimento popular urbano - Psidonik, Jorge Valdair (2019)
The present work consists in the historical rescue of the struggle of Urban Popular Movement (MPU) of Erechim / RS, active, from 2007 to 2016, in the defense of rights to housing of workers who built their houses and their lives on the edge of railroads and BR 153. It aims to understand what were the motivations that resulted in the creation of this Movement, which actions were developed and which factors contributed to the disarticulation of its activities, within the time frame from 1996 to 2016. The organization This Social Movement emerged from the threat of eviction of families due to the possible return of trains and the construction of parallel roads in the urban crossing of BR 153. However, its roots are perceived throughout the process of occupation and struggle for space in the region, begun in 1908, by European immigrants. The economic transformations that occurred throughout the twentieth century, which resulted in a deficit housing, among others, in occupations in various areas of the city of Erechim, such as , roadway anes. The research was articulated around the concept of “moving borders”, with the railroad as the emblematic and paradoxical symbol of the region in the mobility of this border and as a fundamental issue in the struggle for space. The pursuit of progress, modernization and exclusion advanced at the same pace. The same railroad that excluded the “caboclos” from the contested border between Santa Catarina and Paraná at the advent of the twentieth century will exclude the railroad tracks from its shores at the beginning of the 21st century. The methodology used involves bibliographic research, documentary and oral history, through interviews with participants of the Urban Popular Movement, municipal managers, advisors and community leaders who coordinated the process of removal and resettlement of edge of railroads and edge of highway. The study also rescues the process of space occupation in the region of Erechim/RS and the housing policies implemented by the Union and the Municipality. Over the course of three chapters, it demonstrates how people's resistance and struggle for the space dispute promotes achievements that somehow improve their lives, just as the MPU has ensured through its action that families are not evicted and conquered new housing spaces in social subdivisions, thus effecting constitutional rights historically denied to the popular classes.